Integration of corporate data into state monitoring systems for strategic decisions - Zlochovska, Olha (Global Prosperity, 2025)
Abstract. The article explores the integration of corporate data into government monitoring systems aimed at enhancing strategic decision-making in the public sector. The purpose of the study is to substantiate the theoretical and methodological foundations and practical approaches to incorporating corporate data into state monitoring systems in order to increase the efficiency of strategic decision-making in public administration. The research employed general scientific methods of cognition: analysis and synthesis; induction and deduction; system and structural-functional approaches; comparative analysis; as well as methods of generalization and forecasting. The findings show that effective strategic decision-making in the public sector is impossible without a comprehensive data management system combining analytical, ethical, and regulatory components. It is proven that the process of integrating corporate data into government monitoring systems has both technological and institutional dimensions. The study concludes that overcoming the identified barriers is possible through the implementation of modern digital technologies such as artificial intelligence, machine learning, big data analytics, and federated learning. It is found that these tools facilitate the transition from reactive to proactive public governance, improve forecasting accuracy, and reduce cognitive bias risks in policymaking. The study also justifies that applying the principles of responsible data management ensures a balance between technological efficiency, legal legitimacy, and public trust, maintaining ethical equilibrium between public and corporate interests. The experience of the United States, particularly the example of the Health Equity Consortium involving Microsoft and Amazon, demonstrates the effectiveness of bidirectional data exchange within public-private partnerships, which enhances strategic management efficiency, optimizes resource allocation, and produces social benefits. The practical significance of the study lies in the potential to apply its results for creating effective mechanisms of interaction between public and private information systems, thereby promoting transparency and evidence-based strategic governance.